Avaliação da percepção e aderência da população de Fortaleza na transformação para uma cidade inteligente, inclusiva e humana - Gurgel, Paulo Moura Monteiro de Magalhães (2024)
This study investigates the perception of Fortaleza’s citizens regarding the city’s development as a smart city, focusing on inclusion, sustainability, and quality of life. The main objective is to evaluate how technological and sustainable innovations introduced by the public administration impact the population's daily life and to identify the socioeconomic factors that influence the acceptance and engagement with these initiatives. Given the relevance of smart cities in the contemporary urban landscape, the research aims to provide valuable insights for the formulation of public policies that promote an accessible and inclusive technological transformation for all social groups. The methodology adopted included administering a questionnaire through a WhatsApp Chatbot, an accessible and widely used platform, which allowed efficient data collection from a diverse sample of Fortaleza's population. Data analysis was conducted using descriptive and correlational statistics to identify response trends and explore the relationship between demographic variables (such as age, education, income, and location) and the perception of urban innovations. The methodological approach sought to ensure that the responses reflected the population's diversity, providing a broad understanding of the perceptions across different social segments. The results indicate that Fortaleza has made progress in implementing urban technologies and digitizing public services, but these advancements are perceived unequally by the population. Citizens with higher income and education, typically residents of central areas, tend to have a more positive view and greater understanding of these innovations, valuing the benefits associated with smart urban development. Conversely, residents of peripheral areas and lower-income groups face significant barriers to accessing these technologies, with a more limited perception of the benefits of smart city initiatives. These groups often encounter challenges related to digital access and the use of technological devices, limiting their engagement and experience with digital services. The research highlights that digital inclusion and awareness campaigns are essential to ensure that all citizens can benefit from the improvements brought about by the city’s transformation into a smart and sustainable environment. Furthermore, the results show that civic engagement is stronger among citizens who perceive positive impacts from the innovations, suggesting that an effective smart city relies not only on technological infrastructure but also on participatory governance that involves citizens in public decision making. In conclusion, although Fortaleza has made strides toward becoming a smart city, there is an urgent need for policies that promote digital inclusion, reduce inequalities in access to innovations, and encourage active participation from all population segments. The research recommendations emphasize the importance of digital literacy programs, free internet access points in vulnerable areas, and educational campaigns that explain the benefits of technologies in an accessible manner for all. These efforts can consolidate a truly inclusive and sustainable smart city, strengthening citizens' sense of belonging and promoting fair and equitable urban development.